Analysis of slope failure at Maran highway using slope/w software - Annas Robani, Aminudin (2011)
Analysis towards certain slope at Malaysia is important due to many tragedy occurred effect by the slope failure. The purpose of this study is to analyze the slope stability at KM 99 and 101, Maran Highway that carried out by using computer simulation software, slope/ W by Geoslope. The analysis is divided into four (4) different case, which is natural slope condition, protection of slope using slope benching, ground anchor and soil nail method. The computation for the factor of safety is required and from the result achieved; then the proposed slope protection is applied to improve ground stability. The data (Soil Investigation report) collected from the IKRAM Sdn. Bhd. is important to gather the parameter needed for analysis. The output of this study using Morgenstern and Price’s method establishes the FOS value for natural condition of the slope is below the minimum requirement for safe slope which is 0.796. Presence of excess pore water pressure beneath the slope ground layer through rainfall affected the ground stability of the slope. Thus, slope protection must be installed to improve the stability. The result after applying the protection shows the increased in stability; and the highest FOS value is achieved by soil nailing method with 1.591 and followed by anchoring and benching method with 1.229 and 1.164. After safety and economical criteria are considered, soil nailing method is chosen. The immense friction between the soils nails and soil layer produce an additional grip and hold the slope from easily slide.